PRODUKTIVITAS DAN PENDAPATAN USAHATANI PADI SAWAH DAMPAK PROGRAM BANTUAN ALAT MESIN PERTANIAN, BENIH DAN PUPUK DI KABUPATEN MALANG PROVINSI JAWA TIMUR - Prayoga , Adi; Sutoyo, Sutoyo (Jurnal Ilmu-Ilmu Pertanian, 2017)
Study of Productivity and Income of Lowland Rice Farming the Impact of Agricultural machinery Aid, Seeds and Fertilizer is implemented in Malang Regency with sample of location and sample of farmer determined purposively (sampling) in 3 (three) Subdistricts and 6 (six) farmer group who received machinery aid, seeds and fertilizers. The sample of respondents was determined by non-proportioned random sampling method with 15 farmer groups each. Thus, the number of respondents as many as 90 members of the group. This study aims to determine the production, productivity and income of lowland rice farming before and after obtaining agricultural machinery aid, seeds, and fertilizers. Measurement of production is done by weighing the weight of dry grain harvest with tons unit. Productivity is measured by a partial productivity approach that is the production per hectare. Income is analysed using financial analysis. Comparative analysis using Students Test. The results showed that government aid in the form of agricultural machinery, seeds, and fertilizer subsidies can increase production 0.179 tons with an average land area of 0.44 hectares, increase productivity by 0.41 ton / ha or increase 7%, and increase income by Rp2,871,465.00 per hectare or increase 28.96%.